ANALYSIS OF FATIGUE AMONG NURSE EDUCATORS IN BRAZILIAN PUBLIC UNIVERSITIES DURING THE COVID-19 PANDEMIC. - Gutierres-Ruivo, Évilin Diniz; Rocha, Laurelize Pereira; Barlem, Edison Luiz Devos; Sena-Castanheira, Janaína; Cecagno, Diana; Juliano, Laís Farias (Texto & Contexto Enfermagem, 2023)
Objective: to analyze fatigue among nurse educators affiliated with Brazilian public universities while teaching online and hybrid courses during the Covid-19 pandemic. Method: qualitative, cross-sectional study addressing 318 nurse educators teaching in federal and state public universities between July and November 2021. The adapted and validated version of the Three-Dimensional Work Fatigue Inventory (3D-WFI) was used to assess fatigue. The means were compared, and variance analysis (ANOVA) was performed with the Bonferroni test and t-test. The statistically significant variables (p<0.05) remained in the model. Results: the participants were 42 (± 9.4) on average; most were women, 279 (87.7%); 225 (70.8%) had children; and 313 (98.4%) reported performing house chores along with online teaching. In addition to the activities concerning undergraduate programs, 88 (27.7%) participants also performed activities in graduate programs. An association was found between course modality (entirely online or face-to-face, or hybrid) and the dimensions: physical fatigue (p=0.041), mental fatigue (p=0.001), and emotional fatigue (p=0.019), and between taking care of children and help them with school tasks while also teaching classes online and physical fatigue (p=0.012), mental fatigue (p=0.001), and emotional fatigue (p=0.000). Conclusion: the significant differences between course modality and the three dimensions of fatigue (physical, mental, and emotional) showed that the participants experienced physical and mental fatigue during and after work.